Postoperative cardiac troponin I as an indicator of surgical outcomes: A systematic review. Issue 12 (20th November 2022) - Ahmed, Syed Hassan; Pervez, Neha; Rehan, Syeda Tayyaba; Shaikh, Taha Gul; Waseem, Summaiyya
Abstract: Introduction: Cardiac surgeries are generally associated with high morbidity and mortality. To prevent any adverse outcomes, it is crucial to identify patients at risk of developing postoperative complications and initiate relevant therapeutic interventions. Several biomarkers are used to determine postoperative myocardial injury but they either lack sensitivity and specificity or are elevated for a short time. In this systematic review, we evaluate postoperative troponin I as a predictor of postoperative myocardial infarction, mortality, and hospital and Intensive Care Unit stay. Methods: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Review and Meta‐Analysis guidelines. A thorough literature search was conducted over PubMed, clinicaltrials. gov, and the Cochrane library from inception till May 24, 2022 using relevant keywords, and only articles that met the pre‐defined criteria were recruited. Results: Following a comprehensive literature search, a total of 359 articles were obtained. Following a rigid screening and full‐length review, only 13 studies met our inclusion criteria and were included. The recruited studies evaluated data from a total of 12, 483 individuals and assessed troponin I as a predictor of at least one outcome. Conclusion: Troponin I has the potential to be used as a stand‐alone predictor of surgical outcomes following coronary artery bypass grafting and valvular surgeries. However, supplementing it with other markers and scores offers the best chance at timely diagnosing any complications.